Gut dysbiosis in mice genetically selected for low antibody production - Da Silva Santos, Ana Carolina [UNESP]; Jensen, José Ricardo; De Oliveira, Silvio Luis [UNESP]; Rodrigues, Josias [UNESP] (Springer Nature, 2017)
Background: Dysbiosis is linked to the cause of several human diseases, many of which having an immunity related component. This work investigated whether mice genetically selected for low or high antibody production display differences in intestinal bacterial communities, and consisted in the comparison of fecal 16SV6-V8 rDNA PCR amplicons resolved by temperature gradient gel electrophoresis (TGGE) of five each of low (LIII) and high (HIII) antibody producing mice. 16SV6 rDNA amplicons of 2 mice from each line were sequenced. Results: LIII mice were grouped in a single TGGE cluster, displayed a low α-diversity, and were distinguished by low Firmicutes/Bacteroidetes ratio. Conclusion: The results suggest that genetically driven low antibody production in mice is associated with gut dysbiosis.
Keywords: Antibody; Bacteroidetes; Firmicutes; Microbiome; Prevotellaceae; Ruminococcaceae